Green reduction of graphene oxide by polydopamine to a construct flexible film: superior flame retardancy and high thermal conductivity. Issue 35 (18th August 2017) - Luo, Fubin; Wu, Kun; Shi, Jun; Du, Xiangxiang; Li, Xiaoya; Yang, Liu; Lu, Mangeng
Abstract : Inspired by mussels, dopamine (DOPA) was used as a green reducing agent for graphene oxide (GO) to prepare a superior flame retardant and high thermal conductive flexible film. Abstract : Inspired by mussels, dopamine (DOPA) was used as a green reducing agent for graphene oxide (GO) to prepare a superior flame retardant and high thermal conductive flexible film. The self-polymerization of dopamine occurred on the surface of GO nanosheets, accompanied by the reduction of GO. As the solvent was gradually removed, the reduced graphene sheets covered by polydopamine formed a layer-by-layer stacked film, where polydopamine acted as a linkage filled in the interlayer space. Herein, the experimental results indicated that the tensile strength of the constructed graphene/polydopamine composites film (GPF) was as high as 25 MPa. The in-plane thermal conductivity of this prepared film was 13.42 W m −1 K −1, whereas that in the cross-plane direction was 0.69 W m −1 K −1 . The high anisotropy of the thermal conductivity was verified to be due to the high alignment of reduced graphene. Fire experiments showed that the GPF could effectively prevent flame spreading and propagation without ignition, and the heat release rate (HRR) curve showed that the GPF had no heat release below 500 °C. The peak HRR is only 40 W g −1 at 528 °C, whereas that of GO is 360 W g −1 at 165 °C. This phenomenon demonstrates that the GPF has excellent flame retardancy.